Design of Ultra Wideband Antenna Matching Networks Via Simplified Real Frequency Technique - Yarman, Binboga Siddik; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2008)
Design of Ultra Wideband Antenna Matching Networks: via Simplified Real Frequency Technique (SRFT) is the first of its kind and expected to fill a very important gap in the field of wireless communication. It will open up a new horizon for the design engineers, researchers, undergraduate and graduate students to construct multi-band and ultra wideband antenna matching networks for antennas which in turn will push the edge of technology to manufacture new generation of complex communication systems beyond microwave frequencies both in commercial and military line. As opposed to readily available commercial design computer packages, in SRFT, there is no need to choose circuit topology nor need to determine its element values by means of highly non-linear optimization algorithms. Rather, the optimum matching network topology with its element values is obtained as the result of SRFT design process which also yields optimum electrical performance for the matched antenna system. In Design of Ultra Wideband Antenna Matching Networks, many Real life examples are presented to design antenna matching networks over HF and cellular commercial multi-band frequencies. For each example, open MatLab source codes are provided so that the reader can easily generate and verify the results of the examples included in the book. It is expected that the book will be very useful for those who are at the far end the technology and pushes ambitious antenna designs for both military and commercial purposes.
Real Frequency Techniques -- Antenna Fundamentals -- Antennas for Mobile Wireless Communication -- Challenges in Mobile Phone Antenna Development -- Design Techniques for Internal Terminal Antennas -- Terminal Antenna Measurements -- Description of Lossless Two Ports in Terms of Scattering Parameters -- Analytic Approaches to Antenna Matching Problems -- Simplified Real Frequency Technique -- Applications -- Initialization of Simplified Real Frequency Technique -- Analysis and Optimization of Matching Networks-I -- Analysis and Optimization of Matching Networks-II.
Keywords: Electrical engineering; Computer communication systems; Communications Engineering, Networks; Computer Communication Networks